The Australian Breast Cancer Tissue Bank (ABCTB). (24th July 2014) - Carpenter, Jane E; Marsh, Deborah; Mariasegaram, Mythily; Clarke, Christine L
The ABCTB was established in 2006 as an open access, not for profit resource dedicated to providing biospecimens and/or data to both national and international research projects in the field of breast cancer. Donors are consented according to standard ethical principles for use of their material for unspecified future research. ABCTB collects fully annotated clinical samples and associated clinical and longitudinal data from donors. Material and data is supplied to research projects.